SYNTHESIS AND CRYSTAL STRUCTURE OF [PPh ] [WOS (CUNCS) ] (Journal of Sciences, Islamic Republic of Iran)
The reaction of [PPhJ, NOS,] with CuCl and KSCN (1 :3:3) in acetone produces the yell-ow crystals of [PPh,], [WOS,(CuNCS),]. The crystals are triclinic, space group P1(2), z=2, a=12.4823(7), b=12.9224(7), c=18.6395(10)?, ?=83.907(5), ?= 73.152(4), Y= 65.194(4)'. The crystal structure was determined by single crystal Xray diffraction methods (Mo-K ?) and refined by least-squares calculations to a final R-value of 0.062 (R = 0.081) for 1851 unique observed reflections [F>3?|F|]. In [WOS (CuNCS) ] anion the tungsten and copper atoms have essentially a tetrahedral and trigonal planar co-ordination geometry respectively